Kemampuan Guru PAI dalam Menyusun Rencana Pelaksanaan Pembelajaran (RPP) Kurikulum 2013 di SMP Negeri 3 Pantai Labu - Neliwati, Neliwati; Siregar, Evi Rizky Sari; Rangkuti, Rabiatul Adawiyah; Siagian, Muhammad Aldi; Pohan, Nelliana (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
The ability of teachers is very influential in developing the quality of education, especially in compiling lesson plans as study guides. The purpose of writing this journal is to provide knowledge about the importance of the ability of PAI teachers in preparing plans for implementing the 2013 curriculum at SMP Negeri 3 Pantai Labu. This research use desciptive qualitative approach. The results of this study explain that an educator must be able to follow the direction and changes in the curriculum, over time, this curriculum change will bring good value to students, especially to improve the skills and character of students who are religious. Thus, it can be obtained that the abilities that can be mastered by teachers are being able to plan lessons, prepare lesson plans needed in the learning process in the 2013 curriculum, in order to improve the quality and performance of professional teaching.